2023
DOI: 10.1002/cctc.202201126
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Imine Reductases and their Utilisation for the Synthesis of Tetrahydroisoquinolines

Abstract: Imine reductases (IREDs) are NADPH-dependent enzymes with significant biocatalytic potential for the synthesis of primary, secondary, and tertiary chiral amines. Their applications include the reduction of cyclic imines and the reductive amination of prochiral ketones. In this study, twenty-nine novel IREDs were revealed through genome mining. Imine reductase activities were screened at pH 7 and 9 and in presence of either NADPH or NADH; some IREDs showed good activities at both pHs and were able to accept bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Targeting THβCs and THIQs, further discovery and engineering work has revealed the powerful potential of IREDs to catalyze this class of stereoselective synthesis of the sterically demanding molecules (Table 3, entries 38–40). 157–159…”
Section: Imine Reductases and Reductive Aminases (Ireds And Redams)mentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting THβCs and THIQs, further discovery and engineering work has revealed the powerful potential of IREDs to catalyze this class of stereoselective synthesis of the sterically demanding molecules (Table 3, entries 38–40). 157–159…”
Section: Imine Reductases and Reductive Aminases (Ireds And Redams)mentioning
confidence: 99%
“…Targeting THbCs and THIQs, further discovery and engineering work has revealed the powerful potential of IREDs to catalyze this class of stereoselective synthesis of the sterically demanding molecules (Table 3, entries 38-40). [157][158][159] Fig. 17 In 2022, Li et al reported the two-step sequence employing the EREDs and IREDs for the production of N-substituted g-amino esters and g-lactams using cyclopropylamine as the amine partner (Table 3, entry 31).…”
Section: Towards the Applications Of Iredsmentioning
confidence: 99%
“…To broaden the enzyme toolbox, novel IREDs were identified and characterized by Cárdenas-Fernández et al for the reduction of dihydroisoquinolines in the synthesis of tetrahydroisoquinolines (THIQs). [90] In the context of expanding the substrate scope of IREDs acting as reductive aminases, Zheng and coworkers reported an IRED from Penicillium camemberti (PcIRED) able to accept a variety of challenging stericallyhindered amines. [91] The authors also performed protein engineering via iterative saturation mutagenesis guided by an AlphaFold2 model of the PcIRED wild type.…”
Section: Cà N Bond-forming Enzymesmentioning
confidence: 99%
“…Cárdenas-Fernández et al reduced 51a, 51k, and 51r with pQR2595, pQR2600, pQR2601, and pQR2612 which are four D187 subgroup of IREDs (Scheme 64). 76 pQR2600 produced 93% ee of (R)-52a, 84% and 21% yield with and without glucose-6-phosphate dehydrogenase (G6PDH) respectively. Similarly, pQR2601 had shown >99% ee of (R)-52a, 98% and 23% yield with and without G6PDH respectively.…”
Section: Enantioselective Reduction Of 1-substituted-dhiqs By Enzymat...mentioning
confidence: 99%
“…Cárdenas-Fernández et al reduced 51a, 51k, and 51r with pQR2595, pQR2600, pQR2601, and pQR2612 which are four D187 subgroup of IREDs ( Scheme 64 ). 76 …”
Section: Enantioselective Reductions Of 1-substituted-dihydroisoquino...mentioning
confidence: 99%